Dry-Season Fog Water Utilization by Epiphytes in a Subtropical Montane Cloud Forest of Southwest China - Lu-Lu Liu (MDPI AG, 2021)
Fog water is generally considered to be an important water source for epiphytes in cloud forests because they cannot directly access ground-level water sources. However, the water use proportions of potential water sources and water use efficiency of epiphytes in the subtropical montane cloud forests (MCF) remain to be further explored. In this study, we investigated the water use pattern in the dry season and the intrinsic water use efficiency (<semantics>WUEi</semantics>) of four epiphyte groups (i.e., epiphytic lichens, epiphytic bryophytes, epiphytic ferns, and epiphytic seed plants) using stable isotope (δ2H, δ18O, and δ13C) techniques. Our results indicated that the water sources of epiphytes were significantly different among groups and species. The contribution proportions of fog water to epiphytic lichens, epiphytic bryophytes, epiphytic ferns, and epiphytic seed plants were 83.2%, 32.7%, 38.8% and 63.7%, respectively. Epiphytic lichens and epiphytic seed plants mainly depended on fog water whereas the epiphytic bryophytes and epiphytic ferns relied on both fog water and humus. This may be due to their differences in morphological and structural traits (e.g., thallus or leaves, rhizoid or roots). Additionally, the difference in <semantics>WUEi</semantics> was also significant among epiphyte groups and species, which could be related to their different water acquisition patterns. In conclusion, our study reveals the differentiation of water utilization in epiphytes and confirms the importance of fog water for epiphytes during the dry season.